Integrating the Love-Based Curriculum (KBC) and the CASEL Framework: Instructional Strategies in Madrasah Ibtidaiyah - Najwa Nahdiatul Immah; Ariga Bahrodin (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
A Love-based learning approach constitutes an educational mode that integrates the values of compassion, empathy, appreciation, and care into the entirety of the learning process. Its implementation is reinforced by the CASEL framework, which focuses on strengthening the social and emotional competencies of learners. This study aims to elaborate on the strategies employed by teachers, and to identify the supporting factors of CASEL implementation at Madrasah Ibtidaiyah (Islamic elementary school). This research adopted a qualitative approach in the form of a case study. Data were collected through observation, interview, and documentation, and subsequently analyzed through the stages of data reduction, data presentation, and conclusion drawing, with validity verified through source and technique triangulation. The findings reveal that teachers’ strategies are manifested through warm communication, persuasive emotional approaches, and the consistent habituation of positive attitudes, which collectively succeeded in developing students’ social-emotional competencies.